Explaining intention to use an Enterprise Resource Planning (ERP) System : An extension of the UTAUT model - May-Chiun , Lo (-, 2014)
Purpose - This paper proposes an extended model based on the Unified Theory of Acceptance and Use of Technology (UTAUT) developed by Venkatesh et al. (2003) to help better explain the intention to use an Enterprise Resource Planning System (ERP).